Physiological action of certain insecticides and their toxins on isolated cockroach heart - Rao, A. Purushotham; Naidu, M. B. (ENTOMON, 1976)
The physiological action of endrin, malathion and neurotoxins liberated by them was studied on isolated cockroach heart. In the action of malathion acetylcholine is involved and it does not paralyse the cardiac ganglia. Contrary to this malathion neurotoxin acts by paralysing cardiac ganglia and acetylcholine is not involved in its action. Endrin and its neurotoxin act at the cardiac ganglia by paralyzing them and acetylcholine is not involved in their action.